Save our forests - Hirschi, Ron.; Bauer, Erwin A.; Bauer, Peggy (New York : National Audubon Society : Delacorte Press, 1993)
Discusses the characteristics and importance of different kinds of forests and the life they support.
Includes index.
Keywords: Forest ecology -- Juvenile literature; Forest animals -- Juvenile literature; Forest plants -- Juvenile literature; Forest conservation -- Juvenile literature; Forest ecology; Forest animals; Forest plants; Forest conservation